French travelers in Algeria during the 19th century – Eugène Dumas’s travel narrative as a model - zelafi, brahim (El Omda in Linguistics and Discourse Analysis, 2025)
This article aims to introduce some of the French travelers who came to Algeria during the nineteenth century AD, and they were a tool in the hands of the occupation in order to collect information to facilitate its expansion and control over Algerian land, as well as the exploratory missions that the military administration employed and commissioned to conduct a statistical, geographical and historical study of the algerian Sahara. These missions provided sufficient data, maps, and information about southern Algeria, which made it easier for the occupation to penetrate the Algerian desert and tighten its control over the commercial caravan routes.